2011
DOI: 10.1007/s12011-011-9044-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Magnesium Intake and Its Relation with Bone Quality in Healthy Young Korean Women

Abstract: Many studies have reported magnesium's role in nutrition as a vital factor involved in bone health. However, not enough studies have evaluated magnesium (Mg) intakes in young women. In this study, we evaluated Mg intake in healthy adults and its relation with bone quality. A total of 484 healthy young women in their early 20s were enrolled into the study. Anthropometric measurements, dietary intake survey using 3-day dietary records, and the bone quality of the calcaneus using quantitative ultrasounds were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
(36 reference statements)
0
8
0
2
Order By: Relevance
“…Magnesium intake was a significant, independent predictor of bone density in young [ 29 ]. The protective effect of high magnesium intake on bone quality was documented in healthy women using ultrasound measurement in calcaneus [ 30 ]. Moreover, another study in healthy women showed that magnesium intake was positively correlated with bone mass values and it was associated with 12% variability in a bone resorption marker value, deoxypyridinoline in urine [ 31 ].…”
Section: Magnesiummentioning
confidence: 94%
“…Magnesium intake was a significant, independent predictor of bone density in young [ 29 ]. The protective effect of high magnesium intake on bone quality was documented in healthy women using ultrasound measurement in calcaneus [ 30 ]. Moreover, another study in healthy women showed that magnesium intake was positively correlated with bone mass values and it was associated with 12% variability in a bone resorption marker value, deoxypyridinoline in urine [ 31 ].…”
Section: Magnesiummentioning
confidence: 94%
“…Metabolism of magnesium and potassium is linked because magnesium is required for effective Na + /K + -ATPase pump function (17), magnesium and potassium have additive effects in preventing an increase in the endogenous sodium potassium pump inhibitor (16), and both have direct and indirect effects on calcium homeostasis (9,18). Previous studies of the association of dietary magnesium and potassium with bone health have had limited generalizability because of their focus on discrete population groups, such as narrow age range groups of relatively old (5,19) or young individuals (20), restrictions to premenopausal (8,20) or postmenopausal women only (13), and non-United Kingdom residents (5,7,20). Indeed, the most recent and comprehensive study, with a large cohort size and longitudinal analysis of fracture risk, was also limited to women only (7).…”
Section: Introductionmentioning
confidence: 99%
“…A large multiethnic study found that this association may apply to older whites but not blacks 112 . Some studies also found an association with BMD in younger women [113][114] . Study results are mixed with respect to intake and fracture risk 84,110,115 and among Japanese subjects low serum magnesium was associated with increased fracture incidence 116 .…”
Section: Bonementioning
confidence: 92%